2018
DOI: 10.12659/msm.912534
|View full text |Cite
|
Sign up to set email alerts
|

Rs4938723 Polymorphism Is Associated with Susceptibility to Hepatocellular Carcinoma Risk and Is a Protective Factor in Leukemia, Colorectal, and Esophageal Cancer

Abstract: BackgroundGrowing evidence indicates that a non-coding RNA named miR-34b/c plays crucial roles in carcinogenesis, and its common polymorphism, pri-miR-34b/c rs4938723, also participates in this process and is associated with cancer susceptibility. However, this association was previously undefined and ambiguous. Therefore, we carried out an updated analysis to evaluate this relationship between rs4938723 polymorphism and cancer susceptibility.Material/MethodsPubMed, EMbase, Web of Science and Chinese language … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 62 publications
0
4
1
Order By: Relevance
“…Although pre-miR-34b/c polymorphism was previously associated with increased risk in hepatocellular carcinoma 29 and, conversely, with a decreased predisposition to leukemia, colorectal, HNSCC 29 , 30 , and oral cancer 40 , our study did not confirm this. Studies with a larger sample size with the inclusion of gene–gene or gene–environment interactions should be carried out to further elucidate the role of miR-34b/c rs4938723 polymorphism in oral cancer risk.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Although pre-miR-34b/c polymorphism was previously associated with increased risk in hepatocellular carcinoma 29 and, conversely, with a decreased predisposition to leukemia, colorectal, HNSCC 29 , 30 , and oral cancer 40 , our study did not confirm this. Studies with a larger sample size with the inclusion of gene–gene or gene–environment interactions should be carried out to further elucidate the role of miR-34b/c rs4938723 polymorphism in oral cancer risk.…”
Section: Discussioncontrasting
confidence: 99%
“…Recent findings indicate that the expression of miR-34b is decreased in metastatic OSCC compared with nonmetastatic ones 28 , indicating that this microRNA could play an important role in the metastasis of OSCC. Moreover, genetic polymorphism rs4938723, located in the promoter of the pre-miR-34b/c gene, was previously associated with an increased risk of hepatocellular carcinoma 14 , but also with the decreased susceptibility to esophageal cancer, leukemia, and colorectal cancer 29 , 30 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, two meta-analyses revealed that the roles of the miR-34b/c rs4938723 in cancer susceptibility are tissue dependent [20], [55]. The rs4938723 polymorphism was shown to significantly increase the risk of hepatocellular carcinoma but decreased the risk of developing esophageal squamous cell carcinoma, colorectal cancer, and acute lymphoblastic leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…Among the novel candidate genetic variants for the present study is rs4938723, which lies within the potential regulatory region of pri-miR-34b/c and is previously reported to be related to higher risk of PCa (Hashemi et al, 2017[ 14 ]). This potentially functional variant is associated with the risk of cervical, hepatocellular cancer (HCC), childhood acute lymphoblastic leukemia (AML), gastric cancer and esophageal squamose cell carcinoma (ESCC) (Xu et al, 2018[ 36 ]). Similarly, genetic variant rs1076064 which could affect the transcription and/or processing of pri-miR-378 is related to several types of cancer including breast cancer, renal cell cancer (RCC) and AML (Ding et al, 2018[ 9 ]).…”
Section: Introductionmentioning
confidence: 99%